2001
DOI: 10.1001/archotol.127.8.967
|View full text |Cite
|
Sign up to set email alerts
|

Younger Patients Have a Higher Rate of Recovery of Taste Function After Middle Ear Surgery

Abstract: Age is an important factor for recovery of taste function after middle ear surgery, which is useful information when explaining complications to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 9 publications
3
80
1
2
Order By: Relevance
“…The patients with early recovery (within 1 month) were younger (age range 18-55 years, mean 41) than those with a recovery that took longer than 3 months (age range 17-73 years, mean 51; table 1 ). This finding is in agreement with the report of Sone et al [19] , who demonstrated higher recovery rates of taste function in younger patients after middle ear surgery. None of our patients noted any meaningful changes in their quality of life due to taste dysfunction following CI.…”
Section: Discussionsupporting
confidence: 94%
“…The patients with early recovery (within 1 month) were younger (age range 18-55 years, mean 41) than those with a recovery that took longer than 3 months (age range 17-73 years, mean 51; table 1 ). This finding is in agreement with the report of Sone et al [19] , who demonstrated higher recovery rates of taste function in younger patients after middle ear surgery. None of our patients noted any meaningful changes in their quality of life due to taste dysfunction following CI.…”
Section: Discussionsupporting
confidence: 94%
“…Previous attempts of easy and quick clinical taste testing have resulted in the creation of electrogustometry [25], which has been used frequently [40,43,47]. Electrogustometry has proven useful to monitor changes before and after oral surgery and to detect side differences of the tongue's taste function.…”
Section: Discussionmentioning
confidence: 99%
“…The most like cause that can be presumed that, CTN was present and unknowingly injured during surgery. Saito et al 9 suggested that the CTN could have been unknowingly touched or tugged without the surgeon being aware of its existence in the surgical field.…”
Section: Discussionmentioning
confidence: 99%